The Effects of Multinationals? Profit Shifting Activities on Real Investments - Michael Overesch (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2007)
This paper investigates whether the size of multinationals? real investments in a high-tax country is affected by profit shifting activities. A simple theoretical analysis shows that tax rates abroad impact the cost of capital in the presence of profit shifting activities of multinational companies. As profit shifting opportunities constitute a competitive advantage, the respective size of investments should theoretically increase if profits can be shifted to a lower taxing country. An empirical analysis, based on a panel of German inbound investments, confirms a positive tax response of real investments with a decreasing tax rate at the foreign direct investor?s home country. Hence, the results suggest that the size of foreign investments in a high-tax country is positively affected by lower foreign taxation of shifted profits.
Keywords: H32; H25; F23; F21; 330; Taxation; Multinationals; Profit Shifting; Investment Decisions; Firm-level Data; Gewinnverlagerung; Multinationales Unternehmen; Investition; Direktinvestition; Steuerbelastung; Deutschland